THE ROLE OF AMP-ACTIVATED PROTEIN KINASE (AMPK) IN MEDIATING RADIATION RESPONSES IN CANCER CELLS - Sanli, Toran (My University, 2012)
One of the hallmark features of cancer is altered metabolism, whereby rates of glucose and fatty acid turnover are constitutively elevated to support uncontrolled propagation. The key regulator of energy metabolism is the enzyme AMP-activated protein kinase (AMPK), which suppresses anabolic pathways that increase proliferation and enhanced catabolic pathways that liberate energy, all in an attempt to maintain energy homeostasis in the cell. In addition to regulating metabolism, AMPK has also been implicated as a tumour suppressor and we have suggested that it may be a modulator of radiation responses in cancer cells in vitro. Moreover, we investigated the molecular mechanisms that facilitate ionizing radiation (IR)-induced AMPK activation, as well as demonstrated that certain AMPK activating drugs can work as radiation sensitizers in a variety of cancer cell lines. Stemming from this framework, we also provided experimental evidence that suggests AMPK is centrally involved in pathways that regulate DNA damage and proliferation at the basal level, and in response to IR. One of the targets involved in these pathways that can also influence AMPK regulation is the stress-activated Sestrin 2 protein. We have provided evidence that Sestrin 2 mediates IR-induced activation and expression of AMPK. Taken together, this work has provided novel insight into the ability of IR to modulate the activity and expression of AMPK, which in turn is required to facilitate the appropriate stress-response in cancer cells. Given its emerging interest in the cancer field, AMPK may become an important biomarker for evaluating clinical outcomes in patients undergoing radiation therapy.
Keywords: AMPK; ionizing radiation; cancer; metabolism; cell signalling; Medicine and Health Sciences; Medicine and Health Sciences